The role of budABC on 1, 3-propanediol and 2, 3-butanediol production from glycerol in Klebsiella pneumoniae CICIM B0057. Issue 6 (1st November 2016) - Lu, Xinyao; Ji, Guangjian; Zong, Hong; Zhuge, Bin
ABSTRACT: 1, 3-propanediol (1, 3-PD) is an important compound from which many others can be synthesized. 2, 3-butanediol (BDO) is the key by-product in the biosynthesis of 1, 3-PD from glycerol, but it impedes its downstream purification. In Klebsiella, the bud A, bud B and bud C genes encode enzymes that are responsible for the synthesis of BDO. In this study, 3 individual antisense RNAs were designed to repress the expression and hence activity of BudA-C. Compared with the parent strains, the activities of BudB and BudC were reduced by 60.5% and 70.5%, respectively, and the mRNA level of bud A was reduced by 70%. Decreased BudC activity had no effect on cell growth or carbon distribution. However, reduced BudA and BudB activity decreased the BDO concentration by 35% and led to a 10% increase in the yield of 1, 3-PD. This result suggests the activities of BudA and BudB could be key factors in the production of BDO from glycerol in Klebsiella . This study provides a deeper understanding of the role of bud ABC in glycerol metabolism in Klebsiella .